Las mujeres, entre su cuerpo y el mundo. Aproximación antropológica a la vivencia de la salud y el malestar - Esteban, Mari Luz (Estudios humanísticos. Geografía, historia y arte, 1995)
This paper, based upon un anthropological research carried out in the basque urban area, provides an analysis of women’s experiences in relation to health. Within this life area several key questions of women’s subjectivity have been identified, which might help us to gain a better understanding into the situation.